Influence of endogenous female sex-steroids on mutagen metabolism - Goold, Richard David (Rhodes University, Faculty of Pharmacy, Pharmacy, 1985)
Cytochrome P-450, the terminal oxidase of the metabolic mono-oxygenase system, is thought to exist in multiple forms, which have differing substrate specificities, and are variably inducible by different enzyme inducers. Many mutagens, themselves unreactive, require metabolic activation by one or more of these cytochrome P-450-dependent microsomal enzymes for mutagenic activity. Such mutagens may be detected in the Salmonella mutagenicity test only by the incorporation of an hepatic microsomal (59) fraction into the assay (as a first approximation to in vivo metabolism). Induction of the microsomal enzymes by different agents enhances the metabolic activation of mutagens; in fact, many mutagens are only detected when the 59 fraction has been induced by appropriate agents. Inducers of the phenobarbital-type are known to enhance microsomal steroid hydroxylation when administered at supraphysiological levels, inducers of several mono-oxygenase activities. In turn, the steroids, have been reported to be The inductive effects of the female sex-steroids and the combined effects of steroid and phenobarbital (PB) pretreatment on the metabolic activation of four mutagens have been investigated using the Salmonella assay. Female Sprague-Dawley rats were pret reated with 17a-oestradiol (E2) or progesterone (PRG) , at a level of either 1 mg/kg or 20 mg / kg daily for 14 days. A duplicate set of similarly pretreated groups were also induced with PB. Hepatic microsomal fractions were prepared from each group and incubated with each of the te st mutagens in the presence of a tester strain known to detect each particular type of mutagen. Induction of the hepatic metabolizing system by PB increased the activation of the mutagens significantly (as reflected by an increased number of revertant prototrophic S .typhimurium colonies). The administration of PRG also caused significant, and dose-dependent, induction of the activation of af l atoxin B1, benzo(a)pyrene, and dimethylnitrosamine. In general, E2 exhibited no inductive effect, but it did produce an increase in the activation of aflatoxin B1 (a reaction which is known to be catalysed by a mono-oxygenase prefe rentially inducible by PB). When use was made of a microsomal fraction that was prepared from animals which were both steroidpretreated and induced by PB, mutagenic activation was of the same order of magnitude as that observed when induction was brought about by PB alone. The absence of additive effect, taken together with the observations already mentioned, indicate that steroids induce the same cytochrome isozymes that are induced by PB. The implications of sex-hormonal regulation of the metabolic activation of mutagens are briefly discussed.,KMBT_363,Adobe Acrobat 9.53 Paper Capture Plug-in
Keywords: Mutagenesis; Drugs -- Metabolism; Steroid hormones -- Receptors; Cytochrome P-450